Fixed point theorems for operators with a contractive iterate in b-metric spaces: Dedicated to Professor Ioan A. Rus on the occasion of his 80th anniversary - BOTA, Monica-Felicia (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
We consider, in this paper, mappings with a contractive iterate at a point, which are not contractions, and prove some uniqueness and existence results in the case of b metric spaces. A data dependence result and an Ulam-Hyers stability result are also proved. Mathematics Subject Classification (2010): 47H10, 54H25.